Optimization of parallel coiled cavities of different depths in microperforated panel sound absorbers - Hequn Min; Huading Lou; Yuchen Zhao (Scientific Reports)
Abstract This paper presents a microperforated panel (MPP) sound absorber with parallel coiled-up-cavities of different-depths (PCD) and the corresponding optimization on their cavities. In this study, an analytical model is initially proposed for estimating the cavity depths of the PCD-MPP absorber upon normal incidence absorption coefficient evaluation at given resonance frequencies. Cavity effective depths and normal incidence absorption coefficient are evaluated after coiling up cavities for a compact structure. Numerical simulations with the finite element method and experiments are conducted for validations. Subsequently, a design process is suggested on the basis of the proposed model for sound absorption optimization. Results show that, absorption coefficient from the proposed analytical model agrees well with finite element simulations and experiments. It is also shown that, for the effective depth evaluation of the coiled-up cavities of PCD-MPP absorbers, the diagonal lines of subchannels of coiled-up cavities with a coiled-up angle of 180° can accurately represent the effective depths, while the combination of centerlines of subchannels and quarter arc inside the coiled-up area is more suitable for those with a coiled-up angle of 90°. Optimization investigation shows that, PCD-MPP absorbers can have high absorption performance with the averaged and maximum absorption coefficient of 0.91 and 0.98 within the target bandwidth of 400–1600 Hz, where the absorber thickness can stay below 65 mm. This work can provide valuable guidelines for the design of sound absorbers for broadband absorption.